Light-blue thermally activated delayed fluorescent emitters realizing a high external quantum efficiency of 25% and unprecedented low drive voltages in OLEDs. Issue 12 (18th January 2016) - Komatsu, Ryutaro; Sasabe, Hisahiro; Seino, Yuki; Nakao, Kohei; Kido, Junji
Abstract : A series of TADF emitters composed of pyrimidine/acridine moieties are developed. The optimized device realized its highest power efficiency of 62 lm W −1, a high external quantum efficiency of 25%, and a low turn-on voltage of 2.8 V with light-blue emission. Abstract : Thermally activated delayed fluorescent (TADF) emitters are one of the most promising candidates for low-cost and high efficiency organic light-emitting devices (OLEDs) to realize an internal quantum efficiency of unity. However, the power efficiency ( η p ), which is inversely related to the drive voltage, is significantly lower than that of the phosphorescent counterparts, especially for blue devices. Here, we developed a series of TADF emitters, 2-functionalized-4, 6-bis[4-(9, 9-dimethyl-9, 10-dihydroacridine)phenyl]pyrimidine calledAc-RPM . We introduced a phenylacridine moiety into the 4, 6-position of the pyrimidine core to induce a twisted structure leading to a high photoluminescence quantum yield of ∼80%, and a small singlet and triplet excited energy difference of <0.20 eV. The optimized device realized an η p of 62 lm W −1, a high external quantum efficiency of 25%, light-blue emissions with the Commission Internationale de l'Eclairage chromaticity coordinates of (0.19, 0.37) and a low turn-on voltage of <3.0 V.